2022
DOI: 10.3390/ijms23158100
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Velocity (CRPv) as a New Biomarker for the Early Detection of Acute Infection/Inflammation

Abstract: C-reactive protein (CRP) is considered a biomarker of infection/inflammation. It is a commonly used tool for early detection of infection in the emergency room or as a point-of-care test and especially for differentiating between bacterial and viral infections, affecting decisions of admission and initiation of antibiotic treatments. As C-reactive protein is part of a dynamic and continuous inflammatory process, a single CRP measurement, especially at low concentrations, may erroneously lead to a wrong classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
0
16
0
2
Order By: Relevance
“…First, ethical and technical issues limit clinicians from directly obtaining specimens from the lower respiratory tract of sick children [ 20 ]. Second, the use of antibiotics will affect the sensitivity of microbial cultures and may also affect the concentration of inflammatory markers [ 21 ]. Third, owing to the dynamic nature of the infection, the results of testing specimens at different stages of the disease course are likely to vary.…”
Section: Discussionmentioning
confidence: 99%
“…First, ethical and technical issues limit clinicians from directly obtaining specimens from the lower respiratory tract of sick children [ 20 ]. Second, the use of antibiotics will affect the sensitivity of microbial cultures and may also affect the concentration of inflammatory markers [ 21 ]. Third, owing to the dynamic nature of the infection, the results of testing specimens at different stages of the disease course are likely to vary.…”
Section: Discussionmentioning
confidence: 99%
“…Inammatory markers can be used to diagnose and treat inammatory diseases, such as C-reactive protein for diagnosing and monitoring infections and rheumatic diseases. 19 Metabolic markers can be used to diagnose and treat metabolic diseases, such as blood sugar, for diagnosing and monitoring diabetes. 20 The paper divides serum markers into nucleic acids, proteins, and metabolites according to their chemical properties.…”
Section: Serum Markersmentioning
confidence: 99%
“…C-reactive protein is a biomarker of inflammation in the acute response phase stimulated by inflammatory factors such as interleukin-1 (IL-1), IL-6 and tumor necrosis factor (TNF) produced in the liver ( 23 ). CRP is currently widely used mainly in cardiovascular diseases ( 24 ), autoimmune diseases ( 25 ), oncology ( 26 ), and systemic infections ( 27 ), while fewer studies have been performed to predict the occurrence of SIRS after PCNL.…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…However, it is not good in predicting SIRS or sepsis after PCNL compared to PCT ( 21 ), mainly because CRP is more susceptible to rheumatic diseases, malignancies and drug reactions compared to PCT ( 29 ). To address the limited role of CRP in predicting infection, a study found that the CRP-related index C reactive protein velocity (CRPv) (the difference between two CRP measurements before admission divided by the time between the two tests) can better distinguish sepsis from non-sepsis and has a better predictive value ( 23 ). However, there are no studies in which CRPv predicted the occurrence of SIRS after PCNL, so future randomized controlled studies with large samples should be conducted to verify the role of CRPv in predicting SIRS after PCNL.…”
Section: C-reactive Proteinmentioning
confidence: 99%